2015
DOI: 10.1007/s11356-015-5395-5
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic changes in Corbicula fluminea exposed to wastewater from a psychiatric hospital

Abstract: The increase use of pharmaceutical compounds in veterinary practice and human population results in the ubiquitous presence of these compounds in aquatic ecosystems. Because pharmaceuticals are highly bioactive, there is concern about their toxicological effects in aquatic organisms. Therefore, the aim of this study was to assess the effects of an effluent from a psychiatric hospital (containing a complex mixture of 25 pharmaceutical compounds from eleven therapeutic classes) on the freshwater clam Corbicula f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…The movement of electrons is harnessed in the synthesis of ATP, but a slight imbalance of electrons causes ROS [ 90 ]. Regarding metal contamination, studies in Ruditapes philippinarum revealed that a significant number of biological processes (tricarboxylic acid cycle, oxidative phosphorylation, fatty acid β-oxidation, stress resistance, apoptosis and mitochondrial fission) were affected [ 67 ]. In the case of the Corbicula fluminea subjected to pharmaceutical compounds, calreticulin, proliferating cell nuclear antigen, aldehyde dehydrogenase (ALDH), alcohol dehydrogenase, T-complex protein 1 and 6 phosphogluconate dehydrogenase were proposed as protein biomarkers.…”
Section: Proteomic Strategy In the Evaluation Of Bivalves In Polluted...mentioning
confidence: 99%
See 1 more Smart Citation
“…The movement of electrons is harnessed in the synthesis of ATP, but a slight imbalance of electrons causes ROS [ 90 ]. Regarding metal contamination, studies in Ruditapes philippinarum revealed that a significant number of biological processes (tricarboxylic acid cycle, oxidative phosphorylation, fatty acid β-oxidation, stress resistance, apoptosis and mitochondrial fission) were affected [ 67 ]. In the case of the Corbicula fluminea subjected to pharmaceutical compounds, calreticulin, proliferating cell nuclear antigen, aldehyde dehydrogenase (ALDH), alcohol dehydrogenase, T-complex protein 1 and 6 phosphogluconate dehydrogenase were proposed as protein biomarkers.…”
Section: Proteomic Strategy In the Evaluation Of Bivalves In Polluted...mentioning
confidence: 99%
“…In the case of the Corbicula fluminea subjected to pharmaceutical compounds, calreticulin, proliferating cell nuclear antigen, aldehyde dehydrogenase (ALDH), alcohol dehydrogenase, T-complex protein 1 and 6 phosphogluconate dehydrogenase were proposed as protein biomarkers. Metabolism (ALDH, alcohol dehydrogenase and 6 phosphogluconate dehydrogenase) proteins were affected in response to the complex contamination of psychiatric hospital chemical products [ 67 ].…”
Section: Proteomic Strategy In the Evaluation Of Bivalves In Polluted...mentioning
confidence: 99%
“…Regarding the impact of CECs on wild organisms, Bebianno et al [86] used a proteomic approach for the assessment of the response of freshwater clam Corbicula fluminea to effluent from a psychiatric hospital containing a complex mixture of 25 pharmaceuticals. After 1-day exposure, the authors observed an increase in the abundance of structural proteins and calreticulin, as well as proliferation of cell nuclear antigen, T complex protein 1 and aldehyde dehydrogenase, alcohol dehydrogenase, and phosphogluconate dehydrogenase.…”
Section: Proteomics In the Monitoring Of Cec Threats To Freshwater Ecosystems And Analysis Of Cause-effect Relationships-assessment Appromentioning
confidence: 99%
“…Genes involved in xenobiotic detoxification were amongst the most up-regulated genes (Table 3), particularly many isoforms of class III alcohol dehydrogenases (ADH) that are responsible for formaldehyde detoxification by metabolizing glutathione adducts (Haseba et al, 2006). This enzyme involved in Phase 1 xenobiotics metabolism was previously shown to be up-regulated in the digestive gland of bivalves exposed to various organic pollutants, particularly pharmaceuticals (Bebianno et al, 2016;Schmidt et al, 2014). These genes also participate to the KEGG pathway 'Degradation of aromatic compounds' in Table 4, suggesting the presence of organic pollutants in WWTP and runoff waters.…”
Section: Common Transcriptomic Response Of C Fluminea From Both Sitesmentioning
confidence: 99%
“…The Asian freshwater clam Corbicula fluminea is an invasive species, widely distributed in rivers, lakes and estuaries throughout Europe (Sousa et al, 2008). This suspension feeder has been used as a bioindicator to assess the impact of different contaminants, such as metals (Arini et al, 2014) or organic molecules (Bebianno et al, 2016). In the present study, we investigated the transcriptomewide response of field caged specimens to wastewater treatment plant and stormwater runoff effluents in order to get insights on the impacted metabolic pathways and to evaluate the potential use of transcriptomics as early diagnostic tool of water quality in-situ.…”
Section: Introductionmentioning
confidence: 99%